Metals and arsenic in fish from a Ramsar site under past and present human pressures: Consumption risk factors to the local population - Gusso-Choueri, Paloma Kachel [UNESP]; Araujo, Giuliana Seraphim de [UNESP]; Feitosa Cruz, Ana Carolina [UNESP]; Oliveira Stremel, Tatiana Roselena de; Campos, Sandro Xavier de; Souza Abessa, Denis Moledo de [UNESP]; Oliveira Ribeiro, Ciro Alberto de; Choueri, Rodrigo Brasil (Elsevier B.V., 2018)
The risk of metals and As in seafood for traditional populations living in a Marine Protected Areas (MPA) is seldom assessed, although the risk of human exposure to contaminants is one of the indicators associated with the socioeconomic goals of MPAs. The current study aimed to estimate the potential risk of some metals (Cd, Pb, and Zn) and arsenic (As) for human health through the ingestion of fish locally harvested in a Ramsar site, the Cananeia-Iguape-Peruibe Environmental Protected Area (APA-CIP). Previous studies showed environmental impacts in this area due to former mining activities and urbanization. Cathorops spixii, a catfish largely consumed by the local population, was collected along the estuary in three seasons with different rain regimes. Metals and As loads in muscle tissue were quantified and it was estimated (i) the target hazard quotient (THQ) and (ii) the daily intake (EDI) for metals and As, (iii) the cancer risk (CRisk) only for As, and ( iv) the number of eligible meals per month. Cd, Pb, and As were found at concentrations above action levels for human consumption. Depending on the level of exposure of the local population, the consumption of C. spixii may pose risk to human health. Highest THQs were estimated for fish collected in sites closer to the main contamination sources in the APA-CIP, i.e. the mouth of Ribeira de Iguape River (P1) and the city of Cananeia (P4, P5, and P6). Arsenic showed high levels of cancer risk, although restricted to the area close to the city. The exposure of the local population to metal and As contaminated seafood cannot be disregarded in environmental studies and management of the APA-CIP. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Toxic metals; Human exposure; Consumption limits; Allowable daily consumption; Mining activity